DEVELOPING CANVA LEARNING MEDIA TO DEVELOP THE CREATIVE THINKING SKILLS OF CLASS V STUDENTS IN MI - Putri, Mufida Awalia; Nurhayati, Siti; Wulandari, Ratna Wahyu; Adawiya, Robiatul; Maksum, Khanif (PD PGMI se Indonesia, 2024)
Learning media makes it easier for teachers to properly convey messages through learning materials to students and achieve learning objectives. Technological developments such as using learning media can be utilized in education. This study aims to determine the feasibility of Canva-based video media in science learning and the effect of using Canva-based video media on students' creative thinking abilities. The method used is the ADDIE Research and Development (RnD) model, which includes five stages of development: analysis, design, development, implementation, and evaluation. The research was conducted at MI Al Islamiyah Gandekan with a sample of all fifth-grade students. The methods were observation, interview, survey, and test. The research instruments used were pretest and posttest to measure students' creative thinking skills. The results of this study are as follows: (1) developing learning videos using Canva, then validated by experts and used in the learning process; The feasibility of the resulting media is in the very good category with an average score of 3.8. (2) The results of the Mann-Whitney test carried out obtained sig. (2-tailed) 0.048, which means that in this study, there was a significant difference between classes that used video animation and classes that did not use video animation on students' creative thinking abilities. The last stage of the evaluation, which produces feedback from student responses after using the video, gets an average score of 3.6, which is in the very good category.